The Impact of Adaptive Learning Technology on Improving Students’ Concept Understanding - Farida Arinie Soelistianto; Dony Andrasmoro; Yusriati Yusriati; Mardiati Mardiati; Aldi Bastiatul Fawait (Yayasan Adra Karima Hubbi, 2024)
Adaptive learning technology is an educational method that uses artificial intelligence and computer algorithms. This learning system can manage students’ interaction pattern during learning activities. The use of adaptive learning technology is able to change students from just receiving information to an active and collaborative part in the learning process. This research was conducted with the aim of improving the quality of education in Indonesia by encouraging teachers to use this technology. This research also aims to provide a better understanding of the potential and weaknesses of adaptive learning technology in improving students’ concept understanding as well as providing stronger guidance for curriculum development and better educational practices. The method used in this research is quantitative method. This method is a way of collecting numerical data that can be tested. Data is collected through the distribution of questionnaires addressed to students. Furthermore, the data that has been collected from the distribution of the questionnaire, will be accessible in Excel format which can then be processed with SPSS. From the results of the study, it can be seen that the impact of using adaptive learning technology shows that adaptive learning technology can improve the quality of education. Research shows that with the use of adaptive learning technology, it can change teaching methods, learning materials, and can find out the level of learning difficulties faced by these students. From this study, researchers can conclude that the impact of using adaptive learning technology, can improve student understanding and achievement and has the potential to improve the quality of education. with the existence of adaptive learning technology, it is able to increase student involvement and motivation in learning, so that student understanding in learning can be achieved well.